2011
DOI: 10.1063/1.3521488
|View full text |Cite
|
Sign up to set email alerts
|

Excess entropy scaling of transport properties in network-forming ionic melts (SiO $_2$2 and BeF $_2$2)

Abstract: The regime of validity of Rosenfeld excess entropy scaling of diffusivity and viscosity is examined for two tetrahedral, network-forming ionic melts (BeF(2) and SiO(2)) using molecular dynamics simulations. With decrease in temperature, onset of local caging behavior in the diffusional dynamics is shown to be accompanied by a significant increase in the effect of three-body and higher-order particle correlations on the excess entropy, diffusivity, ionic conductivity, and entropy-transport relationships. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 45 publications
3
30
2
Order By: Relevance
“…The upper bound on SiO 2 content and melt conditions (T and P ) at which diffusivities will align with the fit in Fig. 3(a work on supercooled liquids suggests that an equation of the form given by (1) might still be valid in this regime, although with different scaling variables [59][60][61][62].…”
Section: Ear1061e R Ementioning
confidence: 59%
“…The upper bound on SiO 2 content and melt conditions (T and P ) at which diffusivities will align with the fit in Fig. 3(a work on supercooled liquids suggests that an equation of the form given by (1) might still be valid in this regime, although with different scaling variables [59][60][61][62].…”
Section: Ear1061e R Ementioning
confidence: 59%
“…The Rosenfeld scaling relation is found to be valid for a wide variety of liquids including simple liquids 4 , water 22 , ionic melts 5,6,8 , model polymeric melts 3 and even for the data obtained in different experiments [23][24][25] . However the Rosenfeld behaviour is not same for all the systems.…”
Section: Introductionmentioning
confidence: 99%
“…A semi-quantitative relation between dynamical properties like diffusivity or relaxation times and the thermodynamics has been proposed by Rosenfeld 1,2 and recently it has been extensively studied for different systems [3][4][5][6][7][8][9] . The relationship suggests that the fluid should follow X * = C exp[−KS ex ], where X * is the dimensionless dynamical quantity and S ex is excess entropy which is the difference between the total thermodynamic entropy (S tot ) and the corresponding ideal gas entropy (S id ) at the same temperature (T ) and density (ρ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, D Ã is the dimensionless diffusion coefficient normalized by Γd 2 with d being the particle diameter, Γ is the Enskog collision frequency, S 2 is the two-body structural entropy of the system, and A and α are the scaling factors. This universal scaling law has been verified by simulations in simple liquids [15][16][17][18], binary mixtures [19][20][21][22][23], liquid metals [24][25][26][27], and Lennard-Jones chain systems [28]. However, at low densities, it is found that the diffusion coefficients deviate significantly from this relation with much higher values [15,17,[29][30][31].…”
mentioning
confidence: 58%